What makes an information security training project successful? - Szabó, Zsolt (Bánki Közlemények, 2019)
Nowadays project management is a very important part of corporate culture. Organizations recognize that a modern and economical organization cannot be run and maintained without project management. Competitiveness requires processes to be planned, executed, checked and supervised; a basis for the survival of organizations is project management. In large international corporations and organizations, project planning has been considered important for a long time and in Hungary its importance is starting to be recognized. The Hungarian government has worked out an Infocommunications State Secretariat project management methodology in public administration and makes countless recommendations for organizing and running public administration organizations. Nowadays in state organizations, project management methodologies and their application is standard practice. IT security is keeping the IT components of organizational activities in the proper condition to achieve the goals. Security is an essential element of corporate operation – in an organization it is just as important as business conditions. Security is a complex concept; the individual areas are closely related and connected and depend on each other. Information security protects information from many threats (fire, water, other natural disasters, computer hacking, sabotage, software and hardware errors due to improper handling, viruses etc.) in order to ensure business continuity, minimize damage to business, and maximise the possibility of business and return on investment. The paper shows the tasks of project management through an information security training project, using concrete examples. All the selected examples have project-based planning and introduction, and represent project management-based thinking, but taking into account local expectations and exceptions.